Rare but not lost: Endemic mountain lizard occupancy following megafire and grazing disturbances - Hartley, Renée; Blanchard, Wade; Clemann, Nick; Schroder, Mel; Schulz, Martin; Lindenmayer, David B.; Scheele, Ben C. (Austral ecology, 2023)
Wildfire and grazing by invasive herbivores can influence habitat suitability for ground‐dwelling fauna, such as reptiles. Australia has a large and diverse reptile fauna, with the Australian Alps bioregion in the southeast of the continent supporting a disproportionately high number of threatened species. In this bioregion, many species are threatened by fire, habitat loss or modification, and invasive species. The range of one such threatened endemic lizard, Cyclodomorphus praealtus (family Scincidae), was impacted by the 2019–20 megafires and is also subject to widespread grazing by invasive species. We investigated the relationship between C. praealtus site occupancy and fire and grazing. We completed 2045 surveys across 120 sites over 4 years, detecting the species at 43% of sites and increasing the species' known geographic range. Using single season detection occupancy models, we found C. praealtus occupancy was not associated with elevation, vegetation height or whether the site was burnt, but was positively associated with grazing activity. Our results indicate that C. praealtus has the capacity to persist following a single fire in some cases, and that habitats with high occupancy probabilities are subject to high grazing pressure. However, our results do not rule out more nuanced impacts associated with these disturbances, which affect a large proportion of C. praealtus ' habitat. Our cumulative detection probability calculations revealed that considerable survey effort is often required to determine C. praealtus site occupancy. We therefore recommend that impact assessments assume species presence within areas of suitable habitat within the species' range. Our study improves our understanding of disturbance impacts on C. praealtus ' occupancy, while demonstrating the need for sufficiently resourced impact assessments for cryptic and threatened species.